Fuzzy-SMC-PI flux and speed control for induction motors - Mohamed, H.A.F.; Lau, E.L.; Yang, S.S.; Moghavvemi, M. (2008)
This paper presents the design and implementation of Fuzzy-SMC-PI methodology to control the flux and speed of an induction motor. The Fuzzy-SMC-PI is basically a combination of Sliding Mode Control (SMC) and PI control methodologies through fuzzy logic. In this strategy, SMC is responsive during transient state while PI control becomes fully active in the steady state area. This will ensure that the final controller will avoid SMC's inherent chattering problem in steady state and PI's sensitivity, overshoot, long settling time and rise time problems. The combination of both control strategies through fuzzy logic provides a mean to create a hybrid control strategy that produce minimum overshoot, faster settling time and an almost chatter free system. The resulting hybrid system operates by sliding between SMC and PI mode depending on the condition imposed by internal parameter perturbation and external factors such as load torque. Simulations of the proposed Fuzzy-SMC-PI strategy on the flux and speed controllers displayed diminished chatter, overshoot and significant reduction of settling time. One other significant result of applying Fuzzy-SMC-PI strategy on the flux component of the system is that optimum flux level is attained fairly quicker. This resulted in faster rise time and the motor reaching its targeted speed much earlier.